Changing Water Chemistry in One Thousand Norwegian Lakes During Three Decades of Cleaner Air and Climate Change. Issue 2 (30th January 2023) - de Wit, Heleen A.; Garmo, Øyvind A.; Jackson‐Blake, Leah A.; Clayer, François; Vogt, Rolf D.; Austnes, Kari; Kaste, Øyvind; Gundersen, Cathrine Brecke; Guerrerro, Jose Luis; Hindar, Atle
Abstract: We present long‐term changes in Norwegian lake water quality across regional gradients in atmospheric pollution, air temperature, hydrology, and vegetation using (a) a national representative lake survey carried out in 1995 and 2019 (ThousandLakes), and (b) an annual lake survey from acid‐sensitive catchments (78 lakes, TrendLakes) from 1990 to 2020. Our analysis encompasses all major chemical constituents, for example, anions and cations, dissolved organic matter (DOM), nutrients, iron (Fe), and silicate (SiO2 ). During these decades, environmental changes included declines in sulfur (S) and nitrogen (N) deposition, climate warming, and increase in forest biomass. Strong chemical recovery from acidification is found, attributed to large reductions in atmospheric deposition, moderated by catchment processing from land use and climate change. Browning counteracted chemical recovery in some regions, while Ca increased unexpectedly. We suggest that increased weathering, from enhanced terrestrial productivity, is an important driver of increased Ca—substantiated by widespread, substantial increases in SiO2 . Light‐ and nutrient‐limitation has become more prevalent, indicated by higher DOM, lower nitrate (NO3 ), and lower NO3 to total phosphorous ratios. Declines in lake NO3 occurred independently of N deposition, suggesting increased catchment N retention, possibly from increased terrestrial productivity. We conclude that decreased air pollution continues to be a dominant driver of long‐term trends in lake chemistry, but climate‐induced increase in terrestrial weathering processes, governed by increased biomass, is likely to have an increasing impact on future lake acidity, nutrient, and light status, that may cascade along the aquatic continuum from rivers to the coast. Plain Language Summary: Lakes in northern landscapes are sensitive to air pollution and climate change. Here, we investigate how lake water chemistry in a thousand Norwegian lakes has changed since the 1990s, using two large lake monitoring studies from the whole of Norway. Air pollution, climate change, catchment, and lake properties in these data sets are representative of large regions of Europe and North America. We found strong chemical recovery related to reduced atmospheric deposition of sulfur. We also found lower nutrient concentrations due to reduced deposition of nitrogen and increased catchment nutrient retention. The lakes have become less acidic and more nutrient‐ and light‐limited. Unexpectedly, we saw widespread increases in calcium and silicate, which may be linked to increased terrestrial productivity under climate change. Overall, we conclude that air pollution continues to impact boreal lake water quality in addition to climate‐induced changes in terrestrial biogeochemistry. We predict that changes in lake chemistry will continue in the future and will cascade downstream to rivers and coastal areas, with potentially large biological impacts. Key Points: Reduced air pollution is the primary driver of lake chemical change, while climate‐induced changes on element cycling are of secondary importance Strong lake chemical recovery from acidification is demonstrated by reduced SO4 and labile Al and increases in pH, alkalinity, and acid neutralizing capacity Lake display enhanced light‐ and nutrient‐limitation (higher DOM and lower NO3 ), while Ca and SiO2 increased unexpectedly